IMPLEMENTASI STRATEGI PEMBELAJARAN BERDIFERENSIASI PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Halimatussakdiah; Yantoro Yantoro; Muhammad Sholeh (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to describe and analyze the implementation of differentiated learning strategies in science and science learning in elementary schools. The place of this research is SDN 42/IV Jambi City. The subjects of this research were school principals, teachers, and students. The method used is qualitative, with a qualitative phenomenological approach and data collection techniques through observation, interviews, and documentation studies. Data analysis uses the Milles and Huberman approach: data reduction, presentation, and conclusion. Testing the validity of the data uses triangulation techniques. The research results show that implementing differentiated learning strategies in science and science learning in elementary schools begins at the planning, implementation, and evaluation stages. Implementing differentiated learning in science and science learning in elementary schools has been carried out well by paying attention to differentiated elements. Collaboration between various parties continues to be sought to create quality learning and facilitate students to learn according to their readiness, interests, and learning profiles.